Kualitas Layanan, Komunikasi Pemasaran, dan Persepsi Konsumen - Hadir Hudiyanto; Lindawati Lindawati; Ironia Vivie Susanti (The Winners, 2009)
The purpose of this study is to determine the effect of service quality, marketing communications, and consumer perceptions of purchasing decisions. The collecting data through survey and questionnaire used the Likert method. The technique used to take samples was sample of random sampling. The analysis began by testing the validity and reliability to then proceed with the path analysis. The results showed that customer service and marketing communication simultaneously affected consumer perception, with a value of R ² = 0.658. Service quality, marketing communication and consumer perception simultaneously influenced the purchase decision with a value of R ² = 0.617.